2011
DOI: 10.1152/ajpregu.00215.2010
|View full text |Cite
|
Sign up to set email alerts
|

Role of cytochromeP-450 metabolites in the regulation of renal function and blood pressure in 2-kidney 1-clip hypertensive rats

Abstract: Alterations in renal function contribute to Goldblatt two-kidney, one-clip (2K1C) hypertension. A previous study indicated that bioavailability of cytochrome P-450 metabolites epoxyeicosatrienoic acids (EETs) is decreased while that of 20-hydroxyeicosatetraenoic acids (20-HETE) is increased in this model. We utilized the inhibitor of soluble epoxide hydrolase cis-4-[4-(3-adamantan-1-yl-ureido)-cyclohexyloxy]-benzoic acid (c-AUCB) and HET-0016, the inhibitor of 20-HETE production, to study the role of EETs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(70 citation statements)
references
References 59 publications
8
61
1
Order By: Relevance
“…However, restoring EETs did not restore autoregulation (1404), indicating that they were not the cause of defective renal autoregulation. Similarly, 20-HETE participated in basal vasoconstriction, but did not account for the attenuated autoregulation in the unclipped kidney of 2K,1C rats.…”
Section: Goldblatt Renovascular Hypertensionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, restoring EETs did not restore autoregulation (1404), indicating that they were not the cause of defective renal autoregulation. Similarly, 20-HETE participated in basal vasoconstriction, but did not account for the attenuated autoregulation in the unclipped kidney of 2K,1C rats.…”
Section: Goldblatt Renovascular Hypertensionmentioning
confidence: 86%
“…Dogs (1047) and some rats (705,707,1365,1566) with 2K,1C hypertension have maintained RBF and GFR autoregulation in the nonclipped kidney, although other studies in rats have reported weak autoregulation (1188,1404,1494) that was improved by NOS inhibition (1494). Blockade of AT 1 receptors in 2K,1C hypertensive rats did not affect RBF autoregulation in the nonclipped kidney but abolished GFR autoregulation (1566), presumably because of a reduced efferent arteriolar resistance.…”
Section: Goldblatt Renovascular Hypertensionmentioning
confidence: 99%
“…3C). Moreover, HF increased renal 14,15-DHET level, a marker representing sEH activity [20], in the 3-week-old kidney (Fig. 3D).…”
Section: Differential Gene Expression Induced By High Fructosementioning
confidence: 87%
“…The reno-protective effect of sEH inhibition was quite obvious either during the progression of hypertension or after hypertension was established (49 -51, 131). In Goldblatt twokidney, one-clip (2K1C) hypertensive rats, inhibition of sEH decreased blood pressure and sodium excretion together with improved renal blood flow and glomerular filtration rate (GFR) (107,114). Inhibition of sEH also provides renal protection in stroke-prone SHR, as it decreased blood pressure, renal arteriolar hypertrophy, and proteinuria (59).…”
Section: Reno-protective Effects Of Eets In Cvdmentioning
confidence: 99%